2022
DOI: 10.17712/nsj.2022.2.20210125
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry: knowledge, effectiveness, and willingness; assessments of psychiatrists in Saudi Arabia

Abstract: Objectives: To assess psychiatrists' knowledge and perception regarding telepsychiatry and evaluate their willingness to adopt telepsychiatry clinical practice in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This might be owing to their continuing knowledge of the latest developments in healthcare providing. In the same line, Alghamdi et al [ 4 ], who studied telepsychiatry: knowledge, effectiveness, and willingness, assessments of psychiatrists in Saudi Arabia, found that psychiatrists’ knowledge regarding telepsychiatry was deemed insufficient; more than half of the psychiatrists showed a poor level of knowledge regarding telepsychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…This might be owing to their continuing knowledge of the latest developments in healthcare providing. In the same line, Alghamdi et al [ 4 ], who studied telepsychiatry: knowledge, effectiveness, and willingness, assessments of psychiatrists in Saudi Arabia, found that psychiatrists’ knowledge regarding telepsychiatry was deemed insufficient; more than half of the psychiatrists showed a poor level of knowledge regarding telepsychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…One study done on MHWs in SA by AlHadi et al included a similar number of participants (n=1253) [25]. However, others included much smaller samples ranging between 18 and 392 [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of BPD was found to be better among female participants. However, when two studies assessed MHWs' knowledge of electrical convulsive therapy and telepsychiatry in SA, no association between gender and knowledge score was reported [ 27 , 29 ]. This might be explained by the fact that BPD is more prevalent among females, and therefore, females recognize BPD symptomatology more often [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation